Virulence plasmids - Rood, Julian (Henry Stewart Talks, 2008)
Definition and importance of virulence plasmids, Types of virulence plasmids, Toxin plasmids, The anthrax toxin plasmids, Clostridial toxin plasmids, Metabolic plasmids, Mycolactone biosynthesis by Mycobacterium ulcerans, Iron uptake by Vibrio anguillarum, Adhesin plasmids, Enterotoxigenic E. coli: CFA, Enteropathogenic E. coli: BFP, Linear plasmids of Borrelia, Other virulence plasmids, Shigella: type III secretion system, ipa genes, Yersinia: type III secretion system, yop genes, Bacillus anthracis is the causative agent of anthrax, pXO1 encodes toxin and regulatory genes, pXO2 encodes capsule and regulatory genes